2020
DOI: 10.3329/brj.v23i1.46082
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive Rice (Oryza sativa L.) Varieties under Delayed Planting as an Option to Minimize Rice Yield Loss in Flood Affected T. Aman Season

Abstract: Photosensitive rice varieties have higher advantages in delayed planting. The present study was undertaken to figure out the degrees of delayed planting and evaluate the performance of six modern Aman rice varieties (BR11, BR22, BR23, BRRI dhan46, BRRI dhan54) against three sets of delayed planting. Each rice variety showed considerable variations for plant height, days to panicle initiation, flowering and maturity. BR22, BR23, and BRRI dhan54 showed a drastic reduction in days to panicle initiation and varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The crop matured later in the earlier transplanting due to the longer vegetative and reproductive growth but in the delayed of transplanting crop matured earlier due to the shorter growth phase. Similar findings are also reported by Biswas et al [15] that crop maturity duration is steadily reduced with the delay of transplanting.…”
Section: Phenological Parameterssupporting
confidence: 91%
“…The crop matured later in the earlier transplanting due to the longer vegetative and reproductive growth but in the delayed of transplanting crop matured earlier due to the shorter growth phase. Similar findings are also reported by Biswas et al [15] that crop maturity duration is steadily reduced with the delay of transplanting.…”
Section: Phenological Parameterssupporting
confidence: 91%
“…It was the highest during mid-November sowing and the lowest when seeded in mid-January (Table 1). Biswas et al, 2019 reported that late planting causes significant variation in agronomic traits like PI, days to flowering, and days to maturity…”
Section: Panicle Initiation (Pi) and Heading Stagementioning
confidence: 99%
“…Planting rice after the optimal dates may result in lower grain yield due to poor vegetative growth, higher disease and insect incidence, and possible heat or cold damage during heading and grain filling (Groth and Lee, 2003;Reza et al, 2011;Biswas et al, 2019).…”
Section: Growing Degree-days (Gdd)mentioning
confidence: 99%
“…Climatic conditions i.e., cloudy weather, low uptake capacity of fertilizer, lowest growing degree days and short life duration are the main causes of low rice yield of Aman season. Delay planting due to anomalous rainfall, early flood, drought and other climatic hazards causes low yield of Aman rice [26,27] which discourage farmers to cultivate rice in Aman season. Late planting of Aman sometimes hampered the rabi crops (potato, wheat, mustard, vegetables, Boro rice etc.)…”
Section: Plos Onementioning
confidence: 99%